O direito à educação no campo: a voz dos estudantes das escolas do Ribeirão Seco - Itabuna - Bahia - Evangelista, José Carlos Sena (2012)
This research aims to reflect on the guarantee of the right to education in the country, analyzing the contradictions of the discourses of students from the schools in the community of Ribeirão Seco (Itabuna-Bahia). These students are transferred from three schools in Ribeirão Seco Community (rural) to urban schools for continuing education because the community is not offered in regular education from the second segment of the elementary school, very least secondary education. The research was based on the policy of appreciating the "voice" of students of radical pedagogy of Henri Giroux (1988), in culture lived in Raymond Williams (1992) and Terry Eagleton (2005), as well as reflections on the Right to Education Carla Dolphin (2005), Carlos Jamil Cury (2002), Roseli Caldart (2002), Monica Molina (2007) and Adelaide Coutinho (2009). This perspective was presented the speech (voice) of the students in Ribeirão Seco on their schooling, their difficulties in studying the relationship with schools and the right to have school in the field. The results of the analysis of the speech of students is that although the existing educational policy in the city of Itabuna not come to be a denial of their right to school education, is at least a limited access of the majority of the field at the level highest education, consequence of the lack of schools in the final years of primary and secondary education